2019
DOI: 10.1177/000313481908500626
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized Controlled Trials Comparing Lightweight and Heavyweight Mesh for Laparoscopic Total Extraperitoneal Inguinal Hernia Repair

Abstract: The aim of this study was to compare the outcomes of lightweight and heavyweight mesh on postoperative recovery in laparoscopic total extraperitoneal (TEP) inguinal hernia repair. PubMed, Embase, Science Citation Index, and the Cochrane Library were used to search for published clinical randomized controlled trials, which compared lightweight meshes with heavyweight meshes in TEP inguinal hernia repair. The outcomes were calculated as risk ratios with 95 per cent confidence intervals using RevMan 5.2. Eight ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Perhaps more relevant is the collective experience of clinical trials that compare mesh weights for laparoscopic inguinal hernia repair because this mesh is similarly placed in the retromuscular position. Although lightweight mesh has demonstrated limitations in regard to durability for such repairs, these trials have likewise found no difference between rates of pain and foreign-body sensation. Finally, 2 randomized clinical trials comparing mesh weight in open ventral hernia repair likewise found no patient-perceived benefits to the lightweight material.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more relevant is the collective experience of clinical trials that compare mesh weights for laparoscopic inguinal hernia repair because this mesh is similarly placed in the retromuscular position. Although lightweight mesh has demonstrated limitations in regard to durability for such repairs, these trials have likewise found no difference between rates of pain and foreign-body sensation. Finally, 2 randomized clinical trials comparing mesh weight in open ventral hernia repair likewise found no patient-perceived benefits to the lightweight material.…”
Section: Discussionmentioning
confidence: 99%